2021
DOI: 10.1177/0954405421995614
|View full text |Cite
|
Sign up to set email alerts
|

Optimal parameters of abrasive flow finishing for hip joint implants

Abstract: Total hip arthroplasty (THA) is one of the most well-known orthopedic surgeries in the world which involves the substitution of the natural hip joint by prostheses. In this process, the surface roughness of the femoral head plays a pivotal role in the performance of hip joint implants. In this regard, the nano-finishing of the femoral head of the hip joint implants to achieve a uniform surface roughness with the lowest standard deviation is a major challenge in the conventional and advanced finishing processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Kim et al 13 determined the optimum MRF condition for finishing of BK7 glass by varying carrier wheel speed and electromagnetic current and observed that influence function depth increased with increase in carrier wheel speed using different slurry compositions. Choopani et al 14 used the inverse replica fixture technique to finish a femoral head made of a hip joint using an abrasive flow finishing (AFF) setup and reported 99.71% reduction in surface roughness at extrusion pressures of 9.10 MPa, 1000 mesh size of SiC abrasives and 95 finishing cycles. On continuously increasing the rotating speed, Gheisari et al 15 noticed an optimum level of surface roughness with reference to wheel rotation speed.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al 13 determined the optimum MRF condition for finishing of BK7 glass by varying carrier wheel speed and electromagnetic current and observed that influence function depth increased with increase in carrier wheel speed using different slurry compositions. Choopani et al 14 used the inverse replica fixture technique to finish a femoral head made of a hip joint using an abrasive flow finishing (AFF) setup and reported 99.71% reduction in surface roughness at extrusion pressures of 9.10 MPa, 1000 mesh size of SiC abrasives and 95 finishing cycles. On continuously increasing the rotating speed, Gheisari et al 15 noticed an optimum level of surface roughness with reference to wheel rotation speed.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that high finishing uniformity was obtained. 21 The finishing nonuniformity for additively manufactured metal components with variable cross-section flow channels by AFM was studied by Kum et al Results showed that material removal at the necking region with a smaller cross section was much larger than that at other regions with a more spacious cross section. It is believed that when the abrasive medium flows in a channel with decreasing cross section, its wall-slip velocity increases gradually, thus local material removal rate increases, and finishing nonuniformity takes place.…”
Section: Introductionmentioning
confidence: 99%
“…5 On the other hand, advanced finishing processes like magnetic abrasive finishing (MAF) and magnetorheological finishing (MRF) are effectively used to achieve a desired surface finish over the brittle work surface. 6,7 Several authors have started exploring these processes for fragile materials. Jain et al 8 investigated the performance of bonded magnetic-abrasive particles for abrasive finishing.…”
Section: Introductionmentioning
confidence: 99%